Efektivitas Penggunaan Input Dalam Usaha Tani Bawang Merah Di Kecamatan Baraka Kabupaten Enrekang - Wahab, Abdul; Rusydi, Bahrul Ulum; Nirwana, Nirwana (Media Ekonomi, 2021)
The working pattern of shallot farmers in Enrekang Regency still adheres to the old model of production principles, were to increase production is accompanied by adding the inputs. In fact, in the dimension of the Cobb-Douglas production theory, the addition of inputs is not always necessary in line with the increase of production output. Therefore, this study aims to see the effectiveness of inputs in shallots farming in Enrekang Regency. The input variables used in this study include the area of land, capital, labor, and technology that are optimized and correlated with the production of shallots. The analytical method used is multiple linear regression by adopting the Cobb-Douglas production theory. The results of the analysis found that the use of inputs is reaching the condition of decreasing return to scale in shallots farming.